Conceptual Skill Kepala Madrasah - Muhamad Soif (Jurnal Perspektif, 2020)
This paper talked about Conceptual Skill of the School (Madrasah) principals participants of education and Training on Strengthening competences of School principals of South Sumatera, Lampung, Bengkulu, and Babel Provinces. This paper is aimed to know how is the conceptual skills of The school principals participants of the education and training on strengthening competences of the school principals. The analysis was emphasized on descriptive theoritic- emphiric, namely comparing among theory related with the facts and described. The conclusions that the participants on strengthening competnces od the school pricipals was having problem with the conceptual skill, this is probably becoming main reason why Madrasah was still left far behind with another public school.